Clima organizacional y su relación con el desempeño laboral en el personal de la Institución Educativa 601491 Madre Teresa de Calcula año 2023 - Pezo Vela, Gregory Isaac (2024)
The study addresses the problem of organizational climate and work performance in a public entity in the city of Iquitos, considering the importance that the education sector represents in government management. For them, a quantitative study was developed, of an observational type and with a non experimental design that I included the entity's collaborators as the study population, determining the general objective of determining the relationship between the organizational climate and work performance in the staff of the Educational Institution 601491 Mother Teresa of Calcutta, year 2023, the research identified that a positive relationship is presented. strong relationship between the organizational climate and work performance with a Spearman's Rho of 0.791, representing the importance of cultivating a positive and healthy work environment, which presents a strong positive relationship between the organizational climate and work commitment with a Spearman's Rho of 0.851, representing that the need to create a work environment where employees feel valued and motivated is highlighted, that there is a strong positive relationship between the organizational climate and work initiative with a Spearman's Rho of 0.732, which demonstrates the importance to promote an environment in which employees feel strengthened to make decisions and assume responsibilities and that there is a strong positive relationship between the organizational climate and the ability to solve problems with a Spearman's Rho of 0.738 to solve problems, it being relevant to have a work environment that encourages collaboration and creativity.